PENINGKATKAN PRESTASI BELAJAR KEWIRAUSAHAAN MELALUI METODE PEMBELAJARAN KOOPERATIF TEKNIK STAD SMKN 1 SINGOSARI - Trijanawaty, Ririn; Lasiyono, Untung (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
Research on improving entrepreneurship learning achievement through cooperative learning methodof stad technique is done with research population Student of SMK Negeri 1 Singosari, while the sampleof the research is Student of Class XII AB 2 in 2016-2016. In this research, the data were collected intwo stages before the experiment (pre test) and after the experiment (post test). For the respondent stilluse one class that is, the students of class XII AB 2 SMK Negeri 1 Singosari in 2015-2016 with the samebasic competence of preparing business establishment. The result of the research shows that there areincreasing of students 'learning responses and the increase of learners' activity in learning withcontextual approach in the form of group cooperation both in cycle I, II and III. Likewise, learners'responses to learning with a contextual approach also increased both in cycles I, II and III. Alsofollowed with increased learning results consumer protection law. Thus (1) STAD cooperative learningapproach problem posing approach aims to develop students' reasoning and creativity in expressingideas or ideas to integrate the real life of learners. (2) In the first cycle learning is done by conventionallearning method, achievement of student of class XII AB 2 does not have significant difference in resultof pre test and post test. (3) Students' achievement after doing the exercises in the second and thirdcycles using learning approach with problem posing teish shows a significant difference, it is provedand the achievement of pre test result and post test of the participant is known to difference significantly.